Transplantation of tauroursodeoxycholic acid–inducing M2‐phenotype macrophages promotes an anti‐neuroinflammatory effect and functional recovery after spinal cord injury in rats. (7th May 2021) - Han, Gong Ho; Kim, Seong Jun; Ko, Wan‐Kyu; Lee, Daye; Han, In‐Bo; Sheen, Seung Hun; Hong, Je Beom; Sohn, Seil
Abstract: Objectives: In this study, we study the transplantation of tauroursodeoxycholic acid (TUDCA)‐induced M2‐phenotype (M2) macrophages and their ability to promote anti‐neuroinflammatory effects and functional recovery in a spinal cord injury (SCI) model. Methods: To this end, compared to the granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), we evaluated whether TUDCA effectively differentiates bone marrow–derived macrophages (BMDMs) into M2 macrophages. Results: The M2 expression markers in the TUDCA‐treated BMDM group were increased more than those in the GM‐CSF‐treated BMDM group. After the SCI and transplantation steps, pro‐inflammatory cytokine levels and the mitogen‐activated protein kinase (MAPK) pathway were significantly decreased in the TUDCA‐induced M2 group more than they were in the GM‐CSF‐induced M1 group and in the TUDCA group. Moreover, the TUDCA‐induced M2 group showed significantly enhanced tissue volumes and improved motor functions compared to the GM‐CSF‐induced M1 group and the TUDCA group. In addition, biotinylated dextran amine (BDA)–labelled corticospinal tract (CST) axons and neuronal nuclei marker (NeuN) levels were increased in the TUDCA‐induced M2 group more than those in the GM‐CSF‐induced M1 group and the TUDCA group. Conclusions: This study demonstrates that the transplantation of TUDCA‐induced M2 macrophages promotes an anti‐neuroinflammatory effect and motor function recovery in SCI. Therefore, we suggest that the transplantation of TUDCA‐induced M2 macrophages represents a possible alternative cell therapy for SCI. Abstract : Bone marrow–derived monocytes were differentiated into M2‐phenotype (M2) macrophages using tauroursodeoxycholic acid (TUDCA). TUDCA‐induced M2 macrophages were directly transplanted to a lesion in an injured spinal cord. The pro‐inflammatory cytokine levels were significantly decreased in the TUDCA‐induced M2 group. We suggest that the transplantation of TUDCA‐induced M2 macrophages represents a possible alternative cell therapy for SCI.